2014
DOI: 10.1186/2193-1801-3-15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an exercise training intervention with resistance bands on blood cell counts during chemotherapy for lung cancer: a pilot randomized controlled trial

Abstract: PurposeChemotherapy for lung cancer can have a detrimental effect on white blood cell (WBC) and red blood cell (RBC) counts. Physical exercise may have a role in improving WBCs and RBCs, although few studies have examined cancer patients receiving adjuvant therapies. The purpose of this pilot trial was to examine the effects of an exercise intervention utilizing resistance bands on WBCs and RBCs in lung cancer patients receiving curative intent chemotherapy.MethodsA sample of lung cancer patients scheduled for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…103 A 2013 study showed that Tai Chi in lung cancer patients (after resection) altered the ratio of interferon-producing CD 3 to IL-4producing CD 3 . 104 Karvinen et al 105 showed that exercise training may attenuate leukopenia associated with chemotherapy in NSCLC therapy.…”
Section: How Does Activity Help?mentioning
confidence: 99%
“…103 A 2013 study showed that Tai Chi in lung cancer patients (after resection) altered the ratio of interferon-producing CD 3 to IL-4producing CD 3 . 104 Karvinen et al 105 showed that exercise training may attenuate leukopenia associated with chemotherapy in NSCLC therapy.…”
Section: How Does Activity Help?mentioning
confidence: 99%
“…Conversely, the experimental arm (16 postsurgical patients with NSCLC) who followed a guided 16‐week moderate‐intensity tai chi program (60 minutes per session, three sessions per week) managed to preserve a stable T1‐to‐T2 ratio and cortisol levels . Interestingly, preliminary evidence suggests that chemotherapy‐treated patients with lung cancer who joined exercise sessions using resistance bands managed to maintain white blood cell levels during treatment compared with a control group .…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…In another prospective randomized trial, the control group, including 16 patients with surgically resected NSCLC, experienced a decrease in ratio of IFN-γ-producing CD3+ T [107]. Interestingly, preliminary evidence suggests that chemotherapy-treated patients with lung cancer who joined exercise sessions using resistance bands managed to maintain white blood cell levels during treatment compared with a control group [108].…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…Further, patients commonly present with high levels of fatigue, physical impairment and develop neutropenia following chemotherapy [91][92][93][94] ], and may mitigate, restore or reverse side-effects associated with chemotherapy, inclusive of reductions in neutropenia onset, duration and severity of nadir (Fig. 4) following proposed improvements in immune function [97][98][99]. Neoadjuvant and adjuvant exercise therefore has the potential to assist patients to receive their full individual and aggregate doses of chemotherapy, and coupled with posttherapy exercise, may promote bone marrow quality [97] and improve patient physical condition to heighten clinical eligibility to receive and tolerate second-line chemotherapy; two clinically meaningful outcomes for advanced prostate cancer patients that are worthy of exploration.…”
Section: Exercise and Chemotherapymentioning
confidence: 99%
“…4) following proposed improvements in immune function [97][98][99]. Neoadjuvant and adjuvant exercise therefore has the potential to assist patients to receive their full individual and aggregate doses of chemotherapy, and coupled with posttherapy exercise, may promote bone marrow quality [97] and improve patient physical condition to heighten clinical eligibility to receive and tolerate second-line chemotherapy; two clinically meaningful outcomes for advanced prostate cancer patients that are worthy of exploration.…”
Section: Exercise and Chemotherapymentioning
confidence: 99%